LEARNING THE ECONOMIC VOTE AT LOCAL ELECTIONS: CASE OF LITHUANIA, 1995-2011 - Jastramskis, Mažvydas (Baltic Journal of Political Science, 2015)
This paper argues that economic voting is not limited to first-order elections and also can be observed in local elections (usually considered as second-order). Though local governments do not have the power to shape the macro-economic policy of the state, they may have some instruments to influence the well-being of their regions. Moreover, voters may perceive them as accountable for the state of the economy in the region and punish or reward them in local elections on basis of the economic trends. Lithuania appears to be a quite interesting case in which to test these theoretical arguments. Party identification and cleavages are quite weak here: therefore economic voting can be expected to provide at least some explanation of voting (it should not be shadowed by other social factors). Six local municipal council elections were held in Lithuania since the transition to democracy: the first were held in 1995 and the last in 2011. While controlling for important political-contextual factors, this paper strives to compare the impact of economic voting at Lithuania’s municipal elections across time five separate time periods. Results of the empirical analysis reveal that Lithuanians are learning the economic vote with unemployment being more significant as a factor in explaining changes in votes for dominant parties in the municipal councils in the more recent period than in the first several elections. A referendum effect is also observed: parties that belong to the national government parties are punished more during economic downturns.